2017
DOI: 10.3171/2016.1.jns151454
|View full text |Cite
|
Sign up to set email alerts
|

miRNA expression profiling of cerebrospinal fluid in patients with aneurysmal subarachnoid hemorrhage

Abstract: OBJECTIVE MicroRNAs (miRNAs) regulate gene expression and therefore play important roles in many physiological and pathological processes. The aim of this pilot study was to determine the feasibility of extraction and subsequent profiling of miRNA from CSF samples in a pilot population of aneurysmal subarachnoid hemorrhage patients and establish if there is a distinct CSF miRNA signature between patients who develop cerebral vasospasm and those who do not. METHODS CSF samples were taken at various time points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
57
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 57 publications
1
57
0
1
Order By: Relevance
“…However, the implications of miR-27a-3p down-regulation in the pathogenesis of post-ICH complications are unclear. Interestingly, a reduced level of miR-27a-3p was also observed in the cerebrospinal fluid of patients with aneurysmal subarachnoid hemorrhage, and miR-27a-3p reduction was more prominent in those with vasospasm (15). These findings suggest a potential function of miR-27a-3p in the maintenance of cerebrovascular structure and function following hemorrhage.…”
mentioning
confidence: 76%
“…However, the implications of miR-27a-3p down-regulation in the pathogenesis of post-ICH complications are unclear. Interestingly, a reduced level of miR-27a-3p was also observed in the cerebrospinal fluid of patients with aneurysmal subarachnoid hemorrhage, and miR-27a-3p reduction was more prominent in those with vasospasm (15). These findings suggest a potential function of miR-27a-3p in the maintenance of cerebrovascular structure and function following hemorrhage.…”
mentioning
confidence: 76%
“…MicroRNAs are endogenous non-coding RNAs, approximately 18-25 nucleotides in length, which regulate transcriptional gene expression through binding the 3'-untranslated region of mRNAs and the non-translation region in the d-terminus (11). The majority of microRNA genes are located in the exonic, intronic and non-coding regions of the genome, and are transcribed into the microRNA primary transcript by RNA polymerase II, which results in the addition of a poly(A) tail (12).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies of miRNAs in serum and cerebrospinal fluid identified biomarkers associated with occurrence of SAH, including miR‐92a, let‐7b, miR‐204‐5p, miR‐223‐3p, miR‐337‐5p, miR‐451a, miR‐489, miR‐508‐3p, miR‐514‐3p, miR‐516‐5p, miR‐548, miR‐599, miR‐937, miR‐1224‐3p and miR‐1301 . Our previous genomewide serum miRNA expression profiling also suggested that miR‐132‐3p and miR‐324‐3p could be potential biomarkers for SAH . Styllis and others investigated cerebrospinal fluid miRNAs in 10 SAH patients with and 10 without cerebral vasospasm and identified miR‐27a‐3p, miR‐516a‐5p, miR‐566, and miR‐1197 as potential biomarkers for cerebral vasospasm but not DCI .…”
Section: Discussionmentioning
confidence: 81%
“…Our previous genomewide serum miRNA expression profiling also suggested that miR‐132‐3p and miR‐324‐3p could be potential biomarkers for SAH . Styllis and others investigated cerebrospinal fluid miRNAs in 10 SAH patients with and 10 without cerebral vasospasm and identified miR‐27a‐3p, miR‐516a‐5p, miR‐566, and miR‐1197 as potential biomarkers for cerebral vasospasm but not DCI . The identification of miRNAs associated with DCI after SAH has been understudied, hindering understanding and development of therapeutic strategies for DCI after SAH.…”
Section: Discussionmentioning
confidence: 99%